2004
DOI: 10.1111/j.1651-2227.2004.tb00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the C‐terminal region of molecular forms of human milk bile salt‐stimulated lipase

Abstract: Bile salt‐stimulated lipase (BSSL) in human milk exists in multiple molecular forms and it has been shown that approximately one‐third of lactating mothers secrete two forms. Aim: to determine the structural features of BSSL that may give rise to this heterogeneity. Methods: Oligosaccharides present in the proline‐rich region in the C‐terminus of BSSL were investigated using deglycosylating enzymes and lectin affinity probing to determine the origin of the multiple molecular forms. Results: It was found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The sequence coverage was 32% and the probability-based molecular weight search score 199 (with protein scores greater than 76 considered significant). The identification of BSSL is in accordance with the observation that the protein expresses Le X (27).…”
Section: Identification Of Bssl As An Inhibitory Glycoprotein Since mentioning
confidence: 56%
See 3 more Smart Citations
“…The sequence coverage was 32% and the probability-based molecular weight search score 199 (with protein scores greater than 76 considered significant). The identification of BSSL is in accordance with the observation that the protein expresses Le X (27).…”
Section: Identification Of Bssl As An Inhibitory Glycoprotein Since mentioning
confidence: 56%
“…Exon 11 encodes on average 16 repeat domains of 11 amino acids (amino acids 536 to 711) at the C terminus, which contains a high number of O glycosylation sites, while the N terminus contains only one potential N glycosylation site (Asn 187) (1,37). Variant isoforms of BSSL have been shown to differ in the number of repeats at the C terminus of the molecule (24,41), which has been shown to be the domain with a high expression of Le X (27), likely explaining the observed correlation between Le X expression and BSSL size. In accordance with our observation, it has been shown that the expression of Le X can vary between mothers (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bile salt dependent lipase (BSDL) is an LeX-carrying glycoprotein secreted by the pancreas and activated by bile salts in the intestine [9]. BSDL is also expressed by the mammary gland and is present in human milk at a concentration between 100 and 200 μg/ml [10,11].…”
Section: Introductionmentioning
confidence: 99%